PERANAN ETIKA BISNIS DALAM MENEJEMEN KESELAMATAN DAN KESEHATAN KERJA (Manajemen & Bisnis Jurnal, 2019)
In the environment where we live or where we carry out economicactivities, we often find that business activities carried out by a person or a certainbusiness group often ignore the ethics in conducting their activities. Manydeviations are made in line with the purpose of doing business activities only toachieve maximum profits without providing a comfort effect for workers. Many ofthe few business people we meet may not pay attention to their employees,especially in maintaining work safety and safety or easily usually abbreviated asK3 (occupational safety and health). For this reason, every business person needsto pay attention to the role of business ethics in occupational safety and health.With the implementation of the occupational safety and health management system(K3), the company has carried out ethics or is responsible for the worstpossibilities that occur as a result of work activities. The image of companies thathave implemented occupational safety and health management (K3) will get apositive assessment from the community so that they can compete in the global era